2017
DOI: 10.4046/trd.2017.80.2.179
|View full text |Cite
|
Sign up to set email alerts
|

Keratinization of Lung Squamous Cell Carcinoma Is Associated with Poor Clinical Outcome

Abstract: BackgroundAlthough the World Health Organization (WHO) classification of lung squamous cell carcinoma (SCC) was revised in 2015, its clinical implications for lung SCC subsets remain unclear. We investigated whether the morphologic characteristics of lung SCC, including keratinization, were associated with clinical parameters and clinical outcome of patients.MethodsA total of 81 patients who underwent curative surgical resection of diagnosed lung SCC, were enrolled in this study. Attributes such as keratinizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 26 publications
3
23
0
Order By: Relevance
“…We found that the expressions of BCL-xL and let-7a-5p were significantly elevated in lung adenocarcinoma compared with the healthy adjacent control, while there were no significant alterations between lung squamous cell carcinoma and the corresponding control, indicating that dysregulation of BCL-xL and let-7a-5p might only affect the pathogenesis of lung adenocarcinoma, but not lung squamous cell carcinoma. In line with studies previously published, the expression of BCL-xL was not correlated with keratinization, a specific morphologic characteristic that was generally used to indicate the poor clinical outcome of lung squamous cell carcinoma 35 . On the other hand, inhibition of the Bcl-2 family of anti-apoptotic proteins caused a dose-dependent decrease of viability and clonogenicity in A549 lung cancer cells, 36 and downregulation of BCL-xL expression by 25% using an aptamer-targeted BCL-xL shRNA delivery system induced 14% late apoptosis in A549 lung cancer cells 37 …”
Section: Discussionsupporting
confidence: 85%
“…We found that the expressions of BCL-xL and let-7a-5p were significantly elevated in lung adenocarcinoma compared with the healthy adjacent control, while there were no significant alterations between lung squamous cell carcinoma and the corresponding control, indicating that dysregulation of BCL-xL and let-7a-5p might only affect the pathogenesis of lung adenocarcinoma, but not lung squamous cell carcinoma. In line with studies previously published, the expression of BCL-xL was not correlated with keratinization, a specific morphologic characteristic that was generally used to indicate the poor clinical outcome of lung squamous cell carcinoma 35 . On the other hand, inhibition of the Bcl-2 family of anti-apoptotic proteins caused a dose-dependent decrease of viability and clonogenicity in A549 lung cancer cells, 36 and downregulation of BCL-xL expression by 25% using an aptamer-targeted BCL-xL shRNA delivery system induced 14% late apoptosis in A549 lung cancer cells 37 …”
Section: Discussionsupporting
confidence: 85%
“…At an earlier stage, lung SCC is accompanied by epidermal keratinisation. Park et al [64] have provided ample evidence that keratinisation is a significantly poor prognosis factor in lung SCC. Tumour with keratinisation was also more frequently observed among patients with a history of smoking.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, those genes have modest positive correlations with EIF4G1, EIF4A1 and EIF4EBP1, but no correlation with EIF4E in lung tumors. Their biological functions are involved in keratinization (formation of cornified envelope) -a pathological process associated with tumor progression in lung squamous cell carcinoma (Park et al, 2017) -and cell cycle regulation. The strengthened correlations of "cluster one" genes in tumors suggest that EIF4F genes reinforce their regulation of biological pathways that benefit malignancy.…”
Section: Tumors Dysregulate Biological Pathways That Correlate With Ementioning
confidence: 99%